Knowledge relativity: Carnarvon residents’ and SKA personnel’s conceptions of the SKA’s scientific and development endeavours - Butler, Suné Sonia (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.